Burst pressure prediction of multiple cracks in pipelines - Norhaida, Ab. Razak; Nasrul Azuan, Alang; M. A, Murad (2013)
Available industrial code such as ASME B1G, modified ASME B1G and DNV RP- F101 to assess pipeline defects appear more conservative for multiple crack like- defects than single crack-like defects. Thus, this paper presents burst pressure prediction of pipe with multiple cracks like defects. A finite element model was developed and the burst pressure prediction was compared with the available code. The model was used to investigate the effect of the distance between the cracks and the crack length. The coalescence diagram was also developed to evaluate the burst pressure of the multiple crack.It was found as the distance between crack increases ,the interaction effect comes to fade away and multiple cracks behave like two independent single cracks.